Multi-Component Protein Vaccine Induces a Strong and Long-Term Immune Response Against Monkeypox Virus - Xiaolan Yang; Yakun Sun; Hongjing Gu; Deyu Li; Liangyan Zhang; Tao Li; Hui Wang (Vaccines)
Background/Objectives: Since 2022, outbreaks of monkeypox have raised widespread concern and have been declared a public health emergency of international concern by the World Health Organization. There is an urgent need to develop a safe and effective vaccine against the monkeypox virus (MPXV). Recombinant protein vaccines play a significant role in the prevention of infectious diseases due to their high safety and efficacy. Methods: We used the A29, E8, M1, A35, and B6 proteins of MPXV as candidate antigens to generate a panel of multi-component MPXV vaccine candidates, which were administered subcutaneously to immunize mice. Results: The results showed that the vaccine candidates Mix-AEM, Mix-AEMA, Mix-AEMB, and Mix-AEMAB effectively elicited strong neutralizing antibody responses and demonstrated significant protection against vaccinia virus (VACV) infection in a murine model. The vaccine candidate Mix-AEM induced significantly higher levels of neutralizing antibodies, cellular immunity capacity, and virus clearance compared to the vaccine candidate Mix-AE (lacking M1). Single-component immunization showed that M1 induced higher levels of neutralizing antibodies than A29 and E8. These results indicated that M1 is a critical and essential antigen in the MPXV vaccine. The number of cells secreting IFN-γ was significantly increased in the Mix-AEMA and Mix-AEMAB groups compared to the A35-deficient vaccine candidates, demonstrating the important role of A35 in inducing IFN-γ secreting. In addition, the neutralizing antibodies induced by these multi-component vaccine candidates were maintained at high levels six months after the third immunization. Conclusions: In summary, this study lays the groundwork for combining antigens to develop multi-component subunit vaccines.